2008
DOI: 10.1007/s00018-008-8427-1
|View full text |Cite
|
Sign up to set email alerts
|

Origin of pancreatic endocrine cells from biliary duct epithelium

Abstract: We describe an explant culture system to study the formation of pancreatic-type endocrine cells by the biliary tract. In this model, beta-cells and other endocrine cells appear in the biliary duct epithelium and their number increases. Evidence for an origin from the duct epithelium is threefold. Firstly, differentiating cells transiently co-express insulin and bind Dolichos lectin. Secondly, beta-cells in cultures isolated from Alb-Cre-R26R-LacZ mice are beta-galactosidase positive. Thirdly, co-culture of bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In the normal extrahepatic biliary system (24,25) and in certain pathologies involving β-cell neogenesis (26,27), it is possible to find pancreatic endocrine cells budding off ducts, but in our case it is the actual cells of the ducts themselves that are producing the hormones. We have also shown that multihormone-producing cells can exhibit glucose-sensitive insulin secretion.…”
Section: Discussionmentioning
confidence: 71%
“…In the normal extrahepatic biliary system (24,25) and in certain pathologies involving β-cell neogenesis (26,27), it is possible to find pancreatic endocrine cells budding off ducts, but in our case it is the actual cells of the ducts themselves that are producing the hormones. We have also shown that multihormone-producing cells can exhibit glucose-sensitive insulin secretion.…”
Section: Discussionmentioning
confidence: 71%
“…2 and 3). Scattered insulin cells are also found associated with the bile duct as is also found in higher vertebrates (Eberhard et al 2008). No glucagon, PP, or ghrelin (Heller and Christensen 2009) cells have been identified in the structure Fig.…”
Section: Agnatha-cyclostomes: First Appearance Of An Islet Organmentioning
confidence: 74%
“…A possible explanation for this could be the existence of a pancreatic ‘‘stemlike’’ cell capable of giving rise to hepatocytes and originating from duct-like structures. Alternatively, the origin of these cells might lie within the biliary tree, which is known to harbor cells that can contribute to the endocrine lineage (Dutton et al, 2007; Eberhard et al, 2008). The biliary epithelium possesses the ability to form endocrine cells in the absence of Hes-1 , which represses Ngn-3 expression (Sumazaki et al, 2004).…”
Section: Approaches To Restoring β-Cell Function—replenish or Regenermentioning
confidence: 99%